Pengukuran Tingkat Kebisingan Laboratorium pada Perusahaan Daerah Air Minum (PDAM) Tirta Daroy Kota Banda Aceh - Rita Hartati; Marlinda Marlinda; Prasasti Abdillah (Jurnal Optimalisasi, 2021)
Noise is a sound or voice, based on the Decree of the Minister of Manpower and Transmigration of the Republic of Indonesia No. Per.13 / MEN / X / 2011, regarding the average maximum limit in the working area, the average limit of normal hearing in working conditions for 5 hours, a maximum of 87 dB and the standard for laboratory rooms according to the Decree of the Minister of State and Environment No.48 1996 Regarding the Standard Noise Level is 55 dB. PDAM (Regional Drinking Water Company) Tirta Daroy Banda Aceh City is a company that provides clean water for the people of Banda Aceh. PDAM Tirta Daroy has a laboratory that functions as a water quality inspection site. Measurement using a simple method in accordance with the regulation of the Minister of State and Environment No.48 of 1996, the Laboratory of PDAM Tirta Daroy has two roars, namely the testing room and the operator room, the measurement from the test room, the LS (day measurement) value is 62 dB, while the value measurement of the operator space, the value of the LS (day measurement) is 55 dB and the measurement of the average value of the examiner room and the space operator, the value of the LS (day measurement) is 55.20202 dB.